Nanoscale organization of synaptic adhesion proteins revealed by single-molecule localization microscopy - Chamma, Ingrid (Neurophotonics, 2016)
The advent of superresolution imaging has created a strong need for both optimized labeling strategies and analysis methods to probe the nanoscale organization of complex biological structures. We present a thorough description of the distribution of synaptic adhesion proteins at the nanoscopic scale, namely presynaptic neurexin- [Formula: see text] ([Formula: see text]), and its two postsynaptic binding partners neuroligin-1 (Nlg1) and leucine-rich-repeat transmembrane protein 2 (LRRTM2). We monitored these proteins in the membrane of neurons by direct stochastic optical reconstruction microscopy, after live surface labeling with Alexa647-conjugated monomeric streptavidin. The small probe ([Formula: see text]) efficiently penetrates into crowded synaptic junctions and reduces the distance to target. We quantified the organization of the single-molecule localization data using a tesselation-based analysis technique. We show that Nlg1 exhibits a fairly disperse organization within dendritic spines, while LRRTM2 is organized in compact domains, and [Formula: see text] in presynaptic terminals displays a dual-organization pattern intermediate between that of Nlg1 and LRRTM2. These results suggest that part of [Formula: see text] interacts transsynaptically with Nlg1 and the other part with LRRTM2.